Awareness of cardiovascular disease in eastern Saudi Arabia - Nadira A Al-Baghli; Aqeel J AL-Ghamdi; Khalid A Al-Turki; Ahmad G El-Zubaier; Bader A Al-Mostafa; Fadel A Al-Baghli; Mahmood M Al-Ameer (Wolters Kluwer Medknow Publications, 2010)
Objective: To estimate the awareness of cardiovascular disease (CVD) and their determinants in a screening campaign in the eastern province of Saudi Arabia. Materials and Methods: All national residents in the eastern province of Saudi Arabia aged 30 years and above, were invited to participate in a screening campaign for the early detection of diabetes and hypertension at more than 300 examination posts throughout the eastern province. A pre-structured questionnaire was designed to collect data on age, gender, marital status, education level, occupation, lifestyle habits, and history of heart attack, angina, arterial disease, stroke, and transient ischemic attack. Weight, height, blood pressure, and glucose concentration were measured. Results: Out of 197,681 participants, 5372 (2.7%) were aware of a history of a CVD. The prevalence correlated well with age. It was higher in women, widows, and subjects with lower level of education. More than 75% of affected subjects had two or more risk factors. Conclusion: A substantial proportion of those with a history of CVD had multiple risk factors, necessitating an effective, focused policy for the prevention and treatment. Increased effort is required to promote an awareness of cardiac disease and also probably target primary care providers involved in the screening process.